Analisis Komoditi Unggulan di Kabupaten Solok - Gita Ramadhani; Yulhendri Yulhendri (Jurnal Ecogen, 2019)
The aim of this research is to analyze the leading commodities in Solok Regency and to analyze the strategy of developing superior commodities in Solok Regency. This study uses secondary data using a total of 14 research objects in the District of Solok, during the observation year (2013-2017). Data analysis techniques used to analyze superior commodities and analyze strategies for developing superior commodities are using Location Quotient (LQ) and Shift Share analysis techniques. As for processing data using Microsoft Excel. Based on the calculation of LQ and Shift Share to classify commodities, obtained superior or prime commodities in Solok Regency are shallots, carrots and cloves. Keyword: commodity bases, lq, shift share, solok